2020
DOI: 10.1093/ve/veaa091
|View full text |Cite
|
Sign up to set email alerts
|

Novel NGS pipeline for virus discovery from a wide spectrum of hosts and sample types

Abstract: The study of the microbiome data holds great potential for elucidating the biological and metabolic functioning of living organisms and their role in the environment. Metagenomic analyses have shown that humans, along with e.g. domestic animals, wildlife and arthropods, are colonized by an immense community of viruses. The current Coronavirus pandemic (COVID-19) heightens the need to rapidly detect previously unknown viruses in an unbiased way. The increasing availability of metagenomic data in this era of nex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…In this study, we identified viral pathogens from ticks infesting dromedary camels in the Makkah province of Saudi Arabia using a metagenomic approach [ 15 ]. Earlier studies have shown that metagenomic approaches can be used to detect both known and novel viruses associated with animal and human diseases [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified viral pathogens from ticks infesting dromedary camels in the Makkah province of Saudi Arabia using a metagenomic approach [ 15 ]. Earlier studies have shown that metagenomic approaches can be used to detect both known and novel viruses associated with animal and human diseases [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In any case, it is important to continue improving bioinformatic pipelines and databases to be able to screen rapidly metagenomic data and fully identify the organisms in a sample (Nieuwenhuijse et al, 2020;Plyusnin et al, 2020;Dance, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For the construction of complete or nearly complete AMDV sequences, the raw next generation sequencing (NGS) reads were quality-filtered, de novo assembled, and annotated using Trimmomatic, Megahit, and SANSparallel programs, respectively, implemented in Lazypipe pipeline ( Bolger, Lohse, and Usadel 2014 ; Li et al. 2015 ; Somervuo and Holm 2015 ; Plyusnin et al. 2020 ) using default parameters.…”
Section: Methodsmentioning
confidence: 99%